Knowledge, attitudes, and practices on denture maintenance of walk-in removable denture-wearing patients of the University of the Philippines Manila College of Dentistry on the third shift of second semester A.Y. 2017-2018 - De Leon, Vance Lenin B.; Delos Santos, Anna Nikole G.; Jumao-as, Czarina Mikaela C.; Mutia, Jessa Carmela M.; Mendoza, Michael Antonio F. (Manila: Department of Community Dentistry, University of the Philippines Manila, c2018.)
Introduction: Edentulism has a high prevalence rate in the Philippines. Nine million out of 100 million Filipinos are denture wearers. However, there is no published standard protocol and baseline data regarding denture maintenance of removable denture-wearing patients in the Philippines. As a result, there are varying methods of denture maintenance practiced that may be detrimental to the oral health of the patients and to the integrity of the dentures.
Methods: A cross-sectional descriptive study design utilizing self-administered questionnaires was used to obtain data on the knowledge, attitudes, and practices on denture maintenance of walk-in removable denture-wearing patients of the University of the Philippines College of Dentistry.
Results: Majority of the participants were female high school graduates who are 60 years old and above. Most of them have dentures fabricated by a private dentist (57.14%), have 5 to 10 years of denture experience (35.71%), and all have no physical disabilities. The data collected through the self-administered questionnaires showed that the participants got the correct answers to six out of ten questions on knowledge of denture maintenance. Likewise, majority of them (82.14%) consider denture maintenance as very important. The results also showed that the participants practiced what they perceived to be correct in terms of denture maintenance except the necessity to visit the dentist regularly after denture installation.
Conclusions: Based on the results of the study, it can be concluded that the participants had basic knowledge of denture care and they practiced what they perceived to be proper denture maintenance. However, they were lacking in their knowledge and practice of the use of less abrasive denture cleaners like dishwashing liquid. While the use of the toothpaste could clean denture surfaces, it also increases the potential for abrasion. It can also be concluded that most of the participants consider denture maintenance as very important.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila
Keywords: Partial dentures, removable